PENGARUH LATIHAN SUBMAKSIMAL TERHADAP KADAR INTERLEUKIN-6 PADA SISWA PUSAT PENDIDIKAN LATIHAN PELAJAR SUMATERA BARAT - Yuniarti, Elsa (IAIN Batusangkar, 2014)
This study to determine the effect of submaximal exercise on muscle tissue and endothelial damage in athletes indicated by increased levels of IL-6 plasma in the students of The Education Center and Sport Training Student West Sumatera. This study was experimental pre and post-test group design to 17 students sport of football in PPLP West Sumatera. IL-6 before and after exercise submaximal examined was method by ELISA. Statical analysis was bypaired samples t-test and the results obtained statistically significant when p <0,05. The results showed the mean levels IL-6 before the submaximal exercise 4,2±2,8 pg/ml and 7,2±3,6 pg/ml after exercise. The increase levels of IL-6 statistically highly significant p<0,001.Key words : IL-6, submaximal exercise